In Vitro Comparison of Sex-Specific Splicing Efficiencies of fem Pre-mRNA under Monoallelic and Heteroallelic Conditions of csd, a Master Sex-Determining Gene in the Honeybee - Yukihiro Suzuki; Takafumi Yamada; Masataka G. Suzuki (Journal of Developmental Biology, 2023)
The sexual fate of honeybees is determined by the complementary sex determination (CSD) model: heterozygosity at a single locus (the CSD locus) determines femaleness, while hemizygosity or homozygosity at the CSD locus determines maleness. The csd gene encodes a splicing factor that regulates sex-specific splicing of the downstream target gene feminizer (fem), which is required for femaleness. The female mode of fem splicing occurs only when csd is present in the heteroallelic condition. To gain insights into how Csd proteins are only activated under the heterozygous allelic composition, we developed an in vitro assay system to evaluate the activity of Csd proteins. Consistent with the CSD model, the co-expression of two csd alleles, both of which lack splicing activity under the single-allele condition, restored the splicing activity that governs the female mode of fem splicing. RNA immunoprecipitation quantitative PCR analyses demonstrated that the CSD protein was specifically enriched in several exonic regions in the fem pre-mRNA, and enrichment in exons 3a and 5 was significantly greater under the heterozygous allelic composition than the single-allelic condition. However, in most cases csd expression under the monoallelic condition was capable of inducing the female mode of fem splicing contrary to the conventional CSD model. In contrast, repression of the male mode of fem splicing was predominant under heteroallelic conditions. These results were reproduced by real-time PCR of endogenous fem expression in female and male pupae. These findings strongly suggest that the heteroallelic composition of csd may be more important for the repression of the male splicing mode than for the induction of the female splicing mode of the fem gene.